Personal Software Process (PSP) Skills for the Software Industry in Latin America - Pando Soto, Brian Cesar (2020)
This research covers the technical and soft skills required in software development, a globally in-demand activity. These skills are required to efficiently perform in a very globalized, competitive field. Previous studies show the existence of a gap between industry and academia. Training centers provide professionals with technical skills, but as of late, the need for soft skills has become apparent, making it important to study and find ways to embed them into the professionals who join the industry. The application of Personal Software Process (PSP) methodology helps students to strengthen their skills in the software development process, however, the method is not widespread in academia nor industry. This article shows the importance of soft skills, according to Latin American companies, and how PSP can reduce the skills gap.